(untitled) (The Pakistan Development Review, 1982)
This paper confronts the theory of distortions in the factor market with empirical evidence. It is generally concluded that there would not be much to gain in terms of increased production for the economy as a whole from a technically efficient reallocation of labour and capital between industries. However, distortions in the factor market may be of importance in some sectors of the economy which means that imperfections in the factor market should be of concern for economic policy.